HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA SMK NEGERI 3 PAYAKUMBUH PADA MATA PELAJARAN PRODUKTIF TATA KECANTIKAN KULIT - Yulanda, Helfini; Rostamailis, Rostamailis; Astuti, Murni (Journal of Home Economics and Tourism, 2016)
The purpose of this study is to see the relationship between learning motivation with the learning outcomes of students of SMK Negeri 3 Payakumbuh on Beauty Skin Cosmetology productive subjects of students 2014/2015 entry year. This research is a quantitative descriptive-correlation. The population in this study is the entire students of class X and XI of SMK N 3 Payakumbuh in majors Beauty Skin Cosmetology who have followed a productive learning in the 2014/2015 entry year of the total 41 students which is same with the population (total sampling) because the population is less than 100. The technique of getting the data is using the questionnaire with the Liker’t scale which has been tested for validity and reliability. The analysis of the level achievement of the respondents with a percentage formula, whereas the correlation analysis using Pearson Product Moment correlation and continued with t-test to the hypothesis test. Based on the data analysis it’s obtained an average score of respondents to the achievement of the variable learning motivation stand on 61% in lower category and the learning outcomes have an average score that stand on 75 which is under the average value. Both variables relate very strongly with a correlation of 0.803 Ha hypotheses which states there is a positive and significant relationship between learning motivation and learning outcomes in productive subjects received the 95% significance level.Kata Kunci: Motvasi Belajar, Hasil Belajar, Pelajaran Produktif, Tata Kecantikan Kulit.